Evaluation of the control efficacy of antagonistic bacteria from V-Ti magnetite mine tailings on kiwifruit brown spots in pot and field experiments - Cui, Yongliang; Zhu, Yuhang; Dong, Guanyong; Li, Yanmei; Xu, Jing; Cheng, Zuqiang; Li, Lijun; Gong, Guoshu; Yu, Xiumei (Frontiers in Microbiology, 2024)
Seemingly barren heavy-metal-polluted vanadium (V) and titanium (Ti) magnetite mine tailings contain various functional microbes, yet it is unclear whether this includes microbial resources relevant to biological control of plant diseases. Kiwifruit brown leaf spot disease, caused by Corynespora cassiicola, can seriously reduce kiwifruit yield. In an effect to discover effective control measures for kiwifruit leaf spot, eighteen bacteria strains among 136 tailing-isolated bacteria from V-Ti magnetite mine tailings were identified as inhibiting C. cassiicola by the confrontation plate method, indicating that antagonistic bacteria surviving in the V-Ti magnetite mine tailings were present at a low level. The 18 antagonistic strains could be divided into two BOX-A1R clusters. The thirteen representative strains that were selected for phylogenetic tree construction based on their 16S rRNA sequences belonged to the Bacillus genus. Five predominant strains exhibited different toxin-production times and intensities, with four of them initiating toxin production at 32 h. Among them, Bacillus sp. KT-10 displayed the highest bacteriostatic rate (100%), with a 37.5% growth inhibition rate and an antagonistic band of 3.2 cm against C. cassiicola. Bacillus sp. KT10 also showed a significant inhibitory effect against the expansion speed of kiwifruit brown spot appearance in the pot. The relative control effect was 78.48% and 83.89% at 7 days after the first and last spraying of KT-10 dilution, respectively, confirming a good effect of KT-10 on kiwifruit brown leaf spot in the field. This study demonstrated for the first time that there are some antagonistic bacteria to pathogenic C. cassiicola in V-Ti magnetite mine tailings, and Bacillus sp. KT10 was found to be a good control effect on kiwifruit brown leaf spot in pot and field, which provided a effective biological control measurement for kiwifruit brown leaf spot.